Active material for lithium ion batteries and lithium ion batteries
Patent Information
- Application Number
- JP2023080975
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-05-16
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-05-16
AI Technical Summary
【0010】 本開示によれば、最初の充電時の膨張が小さく、かつ充放電を繰り返した場合においても無膨張領域の維持率が高いリチウムイオン電池用活物質、及びそのような活物質を有するリチウムイオン電池を提供することができる。
Smart Images

Figure 0007632513000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an active material for a lithium ion battery and a lithium ion battery. [Background technology]
[0002] In recent years, the development of batteries has been actively carried out. For example, in the automobile industry, development of batteries for use in electric vehicles or hybrid vehicles is underway. Silicon is also known as an electrode active material for batteries, particularly lithium ion batteries.
[0003] Silicon electrode active materials have a large theoretical capacity and are effective in increasing the energy density of batteries. On the other hand, silicon electrode active materials have a problem of large expansion during charging. It is known that the expansion during charging can be suppressed by using a silicon clathrate electrode active material as the silicon electrode active material.
[0004] For example, Patent Document 1 discloses a silicon clathrate electrode active material having a silicon clathrate type II crystal phase, having voids inside primary particles, and having a void volume of pores having a pore diameter of 100 nm or less of 0.05 cc / g or more and 0.15 cc / g or less.
[0005] Patent Document 2 discloses a silicon clathrate electrode active material having primary particles including at least one crystal phase of silicon clathrate I type and silicon clathrate II type, the primary particles having voids therein. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2021-158004 [Patent Document 2] JP 2020-087886 A Summary of the Invention [Problem to be solved by the invention]
[0007] Although silicon clathrate electrode active materials can suppress expansion during charging as compared with ordinary silicon electrode active materials, there is a demand for further suppression of the expansion of silicon clathrate electrode active materials during charging.
[0008] The present disclosure aims to provide an active material for lithium ion batteries that exhibits small expansion during initial charging and has a high retention rate of the non-expansion region even after repeated charging and discharging, and a lithium ion battery having such a battery active material. [Means for solving the problem]
[0009] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> A silicon clathrate having a type I silicon clathrate and a type II silicon clathrate, The ratio of the content of the I-type silicon clathrate to the content of the II-type silicon clathrate is 0.01 Mass % or more 53 Mass % or less, Active material for lithium-ion batteries. <Aspect 2> The ratio is 0.1 Mass % or more 15 Mass 2. The active material for a lithium ion battery according to claim 1, wherein the content of the active material is 0.01 to 0.1%. <Aspect 3> 3. The active material for lithium ion batteries according to claim 1 or 2, wherein a ratio of a mass of the I-type silicon clathrate to a total mass of all components contained in the active material is 0.01 mass % or more and 33 mass % or less. <Aspect 4> 4. The active material for lithium ion batteries according to any one of aspects 1 to 3, wherein the I-type silicon clathrate and / or the II-type silicon clathrate is a porous silicon clathrate. <Aspect 5> A lithium ion battery having a negative electrode active material layer, the negative electrode active material layer comprising the active material for lithium ion batteries according to any one of aspects 1 to 4. Effect of the Invention
[0010] According to the present disclosure, it is possible to provide an active material for a lithium ion battery that exhibits small expansion during initial charging and has a high retention rate of the non-expansion region even after repeated charging and discharging, and a lithium ion battery having such an active material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.
[0012] <Active materials for lithium-ion batteries> The active material for lithium ion batteries of the present disclosure has a silicon clathrate having a type I silicon clathrate and a type II silicon clathrate. The active material for lithium ion batteries of the present disclosure has a silicon clathrate having a type I silicon clathrate and a type II silicon clathrate, and the ratio of the content of the type I silicon clathrate to the content of the type II silicon clathrate is 0.01 or less. Mass % or more 53 Mass % or less
[0013] Compared with the II-type silicon clathrate, the I-type silicon clathrate expands and contracts more when used as a negative electrode active material during charging and discharging. The reason for this is thought to be that, without intending to be bound by any theory, the amount of sodium in the II-type silicon clathrate is less than the amount of sodium in the I-type silicon clathrate. Therefore, based on this premise, when using silicon clathrate as a negative electrode active material, it is thought to be preferable to use only the II-type silicon clathrate and not to have the I-type silicon clathrate present.
[0014] However, the present inventors unexpectedly discovered that by setting the ratio of type I silicon clathrate to type II silicon clathrate within a predetermined range, not only can the expansion of the active material for lithium ion batteries during the initial charge be reduced, but also the expansion during charging after repeated charge and discharge can be reduced.
[0015] The reason for this, without intending to be bound by any theory, is thought to be that the I-type silicon clathrate is thermodynamically more stable than the II-type silicon clathrate, and thus the structural stability during lithium ion insertion is improved.
[0016] In the crystal phase of the I-type silicon clathrate and the II-type silicon clathrate, a polyhedron including a pentagon or hexagon is formed by a plurality of silicon elements. The polyhedron has a space inside that can encapsulate metal ions such as lithium ions. By inserting metal ions into this space, the volume change due to charging and discharging can be suppressed. In addition, since the crystal phase of the I-type silicon clathrate and the II-type silicon clathrate has a space inside that can encapsulate metal ions, there is an advantage that the crystal structure is easily maintained even after repeated charging and discharging.
[0017] An example of a method for confirming that the active material for lithium ion batteries of the present disclosure has a type I silicon clathrate and a type II silicon clathrate is to identify the peaks of each silicon clathrate by X-ray diffraction measurement using CuKα radiation.
[0018] The ratio of the content of the I-type silicon clathrate to the content of the II-type silicon clathrate in the active material for lithium ion batteries of the present disclosure is 0.01 Mass % or more 53 Mass% or less. When this ratio is smaller than the above upper limit, the amount of expansion of the active material for lithium ion batteries during the first charge can be reduced. When this ratio is larger than the above lower limit, the non-expansion region retention rate of the active material for lithium ion batteries after five cycles can be increased. In the present disclosure, the non-expansion region refers to the capacity until the confining pressure starts to increase significantly during charging.
[0019] This ratio is 0.05 Mass % or more, 0.1 Mass % or more, 0.5 Mass % or more, 1.0 Mass % or more, 1.5 Mass % or more, or 2.0 Mass % or more. This percentage may be 50 Mass % or less, 45 Mass % or less, 35 Mass % or less, 25 Mass % or less, 15 Mass % or less, 12 Mass % or less, or 10 Mass % or less.
[0020] The ratio of the mass of the I-type silicon clathrate to the total mass of all components contained in the active material may be 0.01 mass% or more, 0.05 mass% or more, 0.1 mass% or more, 0.5 mass% or more, 1.0 mass% or more, 1.5 mass% or more, or 2.0 mass% or more, and may be 33 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 11 mass% or less, or 10 mass% or less.
[0021] The content of the I-type silicon clathrate and the II-type silicon clathrate can be calculated based on the peak intensity by X-ray diffraction measurement using CuKα radiation. Specifically, it can be calculated using the RIR (Reference Intensity Ratio) method by using Rietveld analysis. PDXL2 manufactured by RIGAKU can be used for the analysis.
[0022] Examples of a method for producing the active material for a lithium ion battery of the present disclosure include, but are not limited to, a method including mixing a silicon raw material and a sodium source and heating the mixture to obtain a powdered sodium silicon (NaSi) alloy, and mixing the obtained NaSi alloy with aluminum fluoride and heating the mixture to obtain a silicon clathrate.
[0023] The sodium source in the process for obtaining a NaSi alloy is exemplified by, but not limited to, sodium hydride.
[0024] The heating temperature in the step of obtaining a NaSi alloy may be 200°C to 700°C, 300°C to 600°C, or 400°C to 500°C.
[0025] The mass ratio of the NaSi alloy to aluminum fluoride in the step of obtaining the silicon clathrate may be 1:0.15 to 1:0.70, 1:0.25 to 1:0.60, or 1:0.35 to 1:0.50.
[0026] The heating temperature in the step of obtaining the silicon clathrate may be 200°C to 500°C, 250°C to 450°C, or 300°C to 400°C.
[0027] The ratio of the I-type silicon clathrate and the II-type silicon clathrate in the active material for lithium ion batteries obtained can be controlled by adjusting the heating temperature in the step of obtaining the NaSi alloy, and the mass ratio of the NaSi alloy and aluminum fluoride in the step of obtaining the silicon clathrate, and the heating temperature. This ratio can also be controlled by dissolving and removing one of the I-type silicon clathrate and the II-type silicon clathrate after the silicon clathrate is produced.
[0028] The I-type silicon clathrate and / or II-type silicon clathrate in the active material for lithium ion batteries of the present disclosure may be a porous silicon clathrate. The porous silicon clathrate can absorb the expansion caused by charging and discharging due to its voids. Therefore, the capacity until the restraining pressure during charging starts to increase significantly, that is, the non-expansion region, can be increased, and the expansion can be reduced.
[0029] In the case where the I-type silicon clathrate and / or the II-type silicon clathrate is a porous silicon clathrate, the method for producing the active material for lithium ion batteries of the present disclosure may be, but is not limited to, the above-mentioned method, which includes mixing silicon and metallic lithium to obtain a lithium silicon (LiSi) alloy, reacting the obtained LiSi alloy with ethanol to obtain porous silicon, and using the obtained porous silicon as a silicon raw material to produce a silicon clathrate as described above.
[0030] Lithium-ion battery The lithium ion battery of the present disclosure may be a liquid battery or a solid-state battery. In the present disclosure, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. The solid-state battery of the present disclosure may also be an all-solid-state battery, i.e., a battery that uses only a solid electrolyte as an electrolyte.
[0031] The lithium ion battery of the present disclosure has a negative electrode active material layer, and the negative electrode active material layer contains the active material for lithium ion batteries of the present disclosure. The lithium ion battery of the present disclosure may also have, in this order, a negative electrode current collector layer, a negative electrode active material layer containing the active material for lithium ion batteries of the present disclosure, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer.
[0032] The lithium ion battery of the present disclosure can be restrained from both sides of the stacking direction of each of the layers by restraining members such as end plates. Examples of the restraining method include, but are not limited to, a method that utilizes the restraining torque of a bolt.
[0033] <Negative electrode current collector layer> The material used for the negative electrode current collector layer is not particularly limited, and any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, copper, a copper alloy, and copper plated or vapor-deposited with nickel, chromium, carbon, or the like may be used, but is not limited to these.
[0034] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0035] <Negative electrode active material layer> The negative electrode active material layer of the present disclosure is a layer containing a negative electrode active material, and optionally a solid electrolyte, a conductive assistant, and a binder. (Negative electrode active material) The negative electrode active material includes the lithium ion battery active material of the present disclosure.
[0036] (solid electrolyte) The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for use in lithium ion batteries can be used. For example, the solid electrolyte may be a sulfide solid electrolyte.
[0037] Examples of sulfide solid electrolytes include, but are not limited to, sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10GeP2S 12 etc.), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li7- x PS6 - x Cl x etc.; or combinations thereof, but are not limited to these.
[0038] The sulfide solid electrolyte may be a glass or a crystallized glass (glass ceramic).
[0039] When the negative electrode active material layer contains a solid electrolyte, the mass ratio of the lithium ion battery active material to the solid electrolyte in the negative electrode active material layer (mass of the lithium ion battery active material:mass of the solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 40:60.
[0040] (Conductive assistant) The conductive assistant is not particularly limited. For example, the conductive assistant may be VGCF (Vapor Grown Carbon Fiber), acetylene black (AB), Ketjen Black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.
[0041] (binder) The binder is not particularly limited. For example, the binder may be a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), or styrene butadiene rubber (SBR), or a combination thereof, but is not limited thereto.
[0042] The negative electrode active material layer may have a thickness of, for example, 0.1 to 1000 μm.
[0043] <Solid electrolyte layer> The solid electrolyte layer includes at least a solid electrolyte. In addition to the solid electrolyte, the solid electrolyte layer may include a binder, etc., as necessary. For the solid electrolyte and the binder, the above description regarding the negative electrode active material layer of the present disclosure can be referred to.
[0044] The thickness of the solid electrolyte layer is, for example, 0.1 to 300 μm, and preferably 0.1 to 100 μm.
[0045] <Cathode active material layer> The positive electrode active material layer is a layer containing a positive electrode active material, and optionally a solid electrolyte, a conductive assistant, a binder, and the like.
[0046] The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y Li-Mn spinel substituted with different elements, which has a composition represented by MyO4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), and lithium titanate (Li x TiO y ), lithium metal phosphate (LiMPO4, M is one or more metals selected from Fe, Mn, Co, and Ni), and the like, but are not limited thereto.
[0047] The positive electrode active material may have a coating layer. The coating layer is a layer containing a substance that has lithium ion conductivity, is low in reactivity with the positive electrode active material and the solid electrolyte, and can maintain the shape of the coating layer without flowing even when it comes into contact with the active material and the solid electrolyte. Specific examples of materials constituting the coating layer include LiNbO3, Li4Ti5O 12 , Li3PO4, etc., but are not limited to these.
[0048] The shape of the positive electrode active material may be, for example, particulate. The average particle size (D50) of the positive electrode active material is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D50) can be calculated, for example, from measurements using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM).
[0049] For the solid electrolyte, the conductive assistant, and the binder, reference can be made to the above descriptions regarding the negative electrode active material layer of the present disclosure.
[0050] When the positive electrode active material layer contains a solid electrolyte, the mass ratio of the positive electrode active material to the solid electrolyte in the positive electrode active material layer (mass of positive electrode active material: mass of solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 50:50.
[0051] The thickness of the positive electrode active material layer is, for example, 0.1 μm to 1000 μm, preferably 1 μm to 100 μm, and more preferably 30 μm to 100 μm.
[0052] <Positive electrode current collector layer> The material used for the positive electrode current collector layer is not particularly limited, and any material that can be used as a positive electrode current collector for a battery can be appropriately adopted. For example, SUS, nickel, chromium, gold, platinum, aluminum, iron, titanium, zinc, etc., and these metals plated or vapor-deposited with nickel, chromium, carbon, etc. may be used, but is not limited to these.
[0053] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred. EXAMPLES
[0054] 《Synthesis of active materials for lithium-ion batteries》 <Alloying> Comparative Example 1 As a silicon (Si) source, Si powder (Kojundo Kagaku, SIEPB32) was prepared. This Si powder and metallic lithium (Li) were weighed out in a molar ratio of Li / Si=4.0, and the weighed Si powder and Li were mixed in a mortar in an argon atmosphere to obtain a lithium silicon (LiSi) alloy. The obtained LiSi alloy was reacted with ethanol in an argon atmosphere and treated with hydrogen fluoride (HF) to obtain a powder having voids inside the primary particles, i.e., a Si powder having a porous structure.
[0055] A sodium silicon (NaSi) alloy was produced using Si powder having a porous structure and sodium hydride (NaH) as a sodium (Na) source. The NaH used was washed with hexane in advance. NaH and Si powder having a porous structure were weighed out so that the molar ratio was 1.05:1, and the weighed NaH and Si powder having a porous structure were mixed in a cutter mill. The resulting mixture was heated in a heating furnace under an argon atmosphere at 400°C for 40 hours to obtain a powdered NaSi alloy.
[0056] <Clathrate formation> The obtained NaSi alloy and aluminum fluoride (AlF3) were weighed out to a molar ratio of 1:0.35, and the weighed NaSi alloy and AlF3 were mixed with a cutter mill to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction vessel, and heated in a heating furnace under an argon atmosphere at 310°C for 60 hours to cause a reaction, thereby obtaining a reaction product containing silicon clathrate. The obtained reaction product was washed with an acid-washed mixed solvent in which HNO3 and H2O were mixed in a volume ratio of 10:90 to remove by-products in the reaction product. After washing, the mixture was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain a powdered reaction product. The obtained material was further washed with a 3wt% HF solution, filtered, and then dried at 120°C for 3 hours or more to obtain the active material for lithium ion batteries of Comparative Example 1. The surface of the active material for lithium ion batteries may contain a coating containing O element, C element, or N element, or impurities such as Fe and Zn.
[0057] (Examples 1 to 3 and Comparative Example 2) The lithium ion battery active materials of Examples 1 to 3 and Comparative Example 2 were obtained in the same manner as in Comparative Example 1, except that in the process of obtaining a NaSi alloy and the process of obtaining a reaction product containing silicon clathrate, the production conditions were changed as shown in Table 1.
[0058] 《Making a lithium-ion battery》 Using the lithium ion battery active material of each example, a lithium ion battery of each example was produced as follows.
[0059] <Formation of negative electrode active material layer> Butyl butyrate, 5wt% butyl butyrate solution of polyvinylidene fluoride (PVDF) binder, vapor grown carbon fiber (VGCF) as a conductive additive, the synthesized active material for lithium ion batteries, and Li2S-P2S5 glass ceramic as a sulfide solid electrolyte were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersing device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.) to obtain a negative electrode composite slurry.
[0060] The obtained negative electrode composite slurry was applied onto a copper (Cu) foil serving as a negative electrode current collector layer by the blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C to form a negative electrode active material layer on the negative electrode current collector layer.
[0061] <Formation of solid electrolyte layer> Heptane, a 5 wt% heptane solution of butylene rubber (BR)-based binder, and Li2SP2S5-based glass ceramic as a sulfide solid electrolyte were added to a polypropylene container and stirred for 30 seconds with an ultrasonic disperser (UH-50, manufactured by SMT Co., Ltd.). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.) to obtain a solid electrolyte slurry.
[0062] The obtained solid electrolyte slurry was applied onto an aluminum (Al) foil as a release sheet by a blade method using an applicator, and dried for 30 minutes on a hot plate heated to 100°C to form a solid electrolyte layer. Three solid electrolyte layers were produced.
[0063] <Formation of Positive Electrode Active Material Layer> A polypropylene container is filled with butyl butyrate, a 5 wt% butyl butyrate solution of a PVDF-based binder, and LiNi with an average particle size of 6 μm as the positive electrode active material. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2S-P2S5-based glass ceramic as a sulfide solid electrolyte, and VGCF as a conductive additive were added to the container and stirred for 30 seconds with an ultrasonic disperser (UH-50, manufactured by SMT Co., Ltd.). Next, the container was shaken for 3 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.), further stirred for 30 seconds with the ultrasonic disperser, and then shaken for 3 minutes with the shaker to obtain a positive electrode composite slurry.
[0064] The obtained positive electrode mixture slurry was applied onto an Al foil serving as a positive electrode current collector layer by a blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C, thereby forming a positive electrode active material layer on the positive electrode current collector layer.
[0065] <Battery Assembly> The positive electrode current collector layer, the positive electrode active material layer, and the first solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 100 kN / cm and a temperature of 165° C. to obtain a positive electrode laminate.
[0066] The negative electrode current collector layer, the negative electrode active material layer, and the second solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 60 kN / cm and a temperature of 25° C. to obtain a negative electrode laminate.
[0067] Furthermore, the Al foil as a release sheet was peeled off from the surfaces of the solid electrolyte layers of the positive electrode laminate and the negative electrode laminate, and then the Al foil as a release sheet was peeled off from the third solid electrolyte layer.
[0068] The positive electrode laminate and the negative electrode laminate were laminated on top of each other so that the solid electrolyte layer of each laminate faced the third solid electrolyte layer, and the laminate was set in a flat uniaxial press and pre-pressed at 100 MPa and 25° C. for 10 seconds, and finally the laminate was set in a flat uniaxial press and pressed at a pressure of 200 MPa and a press temperature of 120° C. for 1 minute, thereby obtaining an all-solid-state battery.
[0069] "evaluation" <XRD measurement> The content ratio of the I-type silicon clathrate and the II-type silicon clathrate in the obtained active material for lithium ion batteries was calculated based on the peak intensity by X-ray diffraction measurement. Specifically, it was calculated using the RIR (Reference Intensity Ratio) method by using Rietveld analysis. In this example, the analysis was performed using PDXL2 of RIGAKU Co., Ltd. Furthermore, the ratio of the content ratio of the I-type silicon clathrate to the content ratio of the II-type silicon clathrate was calculated.
[0070] <Measurement of increase in confining pressure> The fabricated cells were restrained at a predetermined restraining pressure using a restraining jig, and the increase in restraining pressure was measured when the cells were charged at a constant current and constant voltage up to 4.55 V at a 10-hour rate (1 / 10C). A large increase in the restraining pressure means a large expansion of the active material. The increase in the restraining pressure is the difference between the maximum and minimum values of the restraining pressure, and the values in the examples are shown as relative values when the value in Comparative Example 1 is taken as 100.
[0071] <Capacity (non-expansion region) retention rate after 5 cycles> After measuring the increase in the confining pressure, the battery was discharged to 3.0 V at a 1-hour rate (1C), charged at a constant current and constant voltage to 4.35 V at a 3-hour rate (1 / 3C), and discharged at a constant current and constant voltage to 3.0 V at a 3-hour rate (1 / 3C). At that time, the capacity until the confining pressure began to increase significantly during charging was defined as the initial capacity. After that, the same charge and discharge test was repeated five times, and the capacity until the confining pressure began to increase significantly during the fifth charge was defined as the fifth capacity. The capacity (non-expansion region) retention rate after five cycles was calculated by dividing the fifth capacity by the initial capacity.
[0072] "result" The content ratios of the I-type silicon clathrate and the II-type silicon clathrate in the active material for lithium ion batteries, the ratio of the I-type silicon clathrate content to the II-type silicon clathrate content, the results of the XRD measurement, the measurement results of the increase in confining pressure, and the calculation results of the capacity (non-expansion region) maintenance rate after 5 cycles are shown in Table 1. In Table 1, "I-type" means I-type silicon clathrate, and "II-type" means II-type silicon clathrate.
[0073] [Table 1]
[0074] As shown in Table 1, the batteries of Examples 1 to 3, in which the ratio of type I silicon clathrate to type II silicon clathrate is within the range of the present disclosure, had a smaller increase in confining pressure than Comparative Example 1, in which this ratio is greater than the range of the present disclosure, and had a higher capacity (non-expansion region) retention rate after 5 cycles than Comparative Example 2, in which this ratio is less than the range of the present disclosure.
Claims
1. A silicon clathrate having a type I silicon clathrate and a type II silicon clathrate, The ratio of the content of the I-type silicon clathrate to the content of the II-type silicon clathrate is 0.01% by mass or more and 15% by mass or less; Active material for solid-state lithium-ion batteries.
2. The active material for a solid lithium ion battery according to claim 1 , wherein the ratio is 0.1% by mass or more and 12% by mass or less.
3. The total mass of the I-type silicon clathrate contained in the active material The active material for a solid lithium ion battery according to claim 1, wherein the ratio of the total mass of the above is 0.01 mass% or more and 33 mass% or less.
4. 2. The active material for a solid lithium ion battery according to claim 1, wherein the I-type silicon clathrate and / or the II-type silicon clathrate is a porous silicon clathrate.
5. A solid-state lithium-ion battery having a negative electrode active material layer, the negative electrode active material layer comprising the active material for a solid-state lithium-ion battery according to any one of claims 1 to 4.
6. A silicon clathrate having a type I silicon clathrate and a type II silicon clathrate, The ratio of the content of the I-type silicon clathrate to the content of the II-type silicon clathrate is 0.01 mass% or more and 15 mass% or less; and The ratio of the mass of the I-type silicon clathrate to the total mass of all components contained in the active material is 0.01 mass% or more and 15 mass% or less (excluding 1.4 mass%). Active material for lithium-ion batteries.
7. 7. The active material for lithium ion batteries according to claim 6, wherein the ratio of the content of the I-type silicon clathrate to the content of the II-type silicon clathrate is 0.1 mass% or more and 12 mass% or less.
8. The active material for lithium ion batteries according to claim 6 , wherein the I-type silicon clathrate and / or the II-type silicon clathrate is a porous silicon clathrate.
9. A lithium ion battery having a negative electrode active material layer, the negative electrode active material layer comprising the active material for lithium ion batteries according to any one of claims 6 to 8.
Citation Information
Patent Citations
Active material, battery and method for producing active material
JP2020087886A
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158004A
Method for manufacturing negative electrode active material
JP2023043948A
Type ii clathrates for rechargeable battery anodes
US20150380724A1